Aptamer-integrated DNA nanostructures for biosensing, bioimaging and cancer therapy. (8th March 2016) - Meng, Hong-Min; Liu, Hui; Kuai, Hailan; Peng, Ruizi; Mo, Liuting; Zhang, Xiao-Bing
Abstract : We survey advances in biosensing, bioimaging and cancer therapy applications of aptamer-integrated DNA nanostructures in this review. Abstract : The combination of nanostructures with biomolecules leading to the generation of functional nanosystems holds great promise for biotechnological and biomedical applications. As a naturally occurring biomacromolecule, DNA exhibits excellent biocompatibility and programmability. Also, scalable synthesis can be readily realized through automated instruments. Such unique properties, together with Watson–Crick base-pairing interactions, make DNA a particularly promising candidate to be used as a building block material for a wide variety of nanostructures. In the past few decades, various DNA nanostructures have been developed, including one-, two- and three-dimensional nanomaterials. Aptamers are single-stranded DNA or RNA molecules selected by Systematic Evolution of Ligands by Exponential Enrichment (SELEX), with specific recognition abilities to their targets. Therefore, integrating aptamers into DNA nanostructures results in powerful tools for biosensing and bioimaging applications. Furthermore, owing to their high loading capability, aptamer-modified DNA nanostructures have also been altered to play the role of drug nanocarriers for in vivo applications and targeted cancer therapy. In this review, we summarize recent progress in the design of aptamers and related DNA molecule-integrated DNA nanostructures as well as their applications in biosensing, bioimaging and cancer therapy. To begin with, we first introduce the SELEX technology. Subsequently, the methodologies for the preparation of aptamer-integrated DNA nanostructures are presented. Then, we highlight their applications in biosensing and bioimaging for various targets, as well as targeted cancer therapy applications. Finally, we discuss several challenges and further opportunities in this emerging field.